2013
DOI: 10.1080/09540121.2013.855303
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk perception among pregnant women in western India: Need for reducing vulnerabilities rather than improving knowledge!

Abstract: Since the beginning of the HIV/AIDS epidemic in India, pregnant women attending antenatal clinics (ANC) have been considered as a low HIV risk population. Yet, a substantial proportion of new HIV infections are occurring among stable heterosexual couples. This paper sought to investigate the proportion and profile of women who, within the low-risk population, are potentially at higher risk of HIV infection. HIV risk perception of pregnant women enrolled within the ANRS 12127 Prenahtest trial was described and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
1
2
Order By: Relevance
“…They also had a realistic perception of the risks of both home delivery and of mother-to-child transmission of HIV, which guided them to choose facility delivery regardless of their HIV status. This is in line with findings from Nigeria and India showing high levels of awareness of HIV-related issues among women of reproductive age (Olugbenga-Bello et al 2013;Darak et al 2014).…”
Section: Individual Levelsupporting
confidence: 93%
“…They also had a realistic perception of the risks of both home delivery and of mother-to-child transmission of HIV, which guided them to choose facility delivery regardless of their HIV status. This is in line with findings from Nigeria and India showing high levels of awareness of HIV-related issues among women of reproductive age (Olugbenga-Bello et al 2013;Darak et al 2014).…”
Section: Individual Levelsupporting
confidence: 93%
“…The rate of HIV-2 and HIV-D was higher compared to HIV-1 in non-literate women while HIV-1 prevailed among women in the primary level. These results contrast with those of Ghana where women of secondary and tertiary level were less likely to be infected with HIV than those without primary education (OR = 0.53) [57] and India which revealed that women with less than 11 years of formal education were more likely to have HIV (Adjusted Odds Ratio=2.4). [58] They are comparable with the highest prevalence (13.4%) and 3.9% among non-literate women in Tanzania respectively [56] and Uganda [54].…”
Section: Rate Of Hiv-1 Hiv-2 and Hiv-d By Socio-demographic Charactecontrasting
confidence: 54%
“…This result is different from that mentioned in Uganda stipulating that students had higher risk of HIV infection (AIRR=0.22) [59]. However, it is comparable to other studies especially in Burkina Faso where pupils and students be exposed to the risk of HIV infection was higher (OR=1.68 [1.20 to 2.33]) compared to other types of occupation gathered [41]; in Tanzania where prevalence was higher (13.1%) in commercial [53] [57] women of secondary and tertiary levels had a higher risk of being infected with HIV than those who did not reach the primary level (OR=0.5) and in India suggesting that women with less than 11 years of schooling had less risk of infection (Adjusted Odds Ratio=2.4) [58].…”
Section: Risk Factors Associated With Hiv-1 Hiv-2 and Hiv-d In Womencontrasting
confidence: 54%
“…Participants with higher perceived HIV risk were also more likely to initiate PrEP, though overall <10% perceived themselves to be at high risk for HIV. Previous studies have shown an imbalanced relationship between perceived vs. actual HIV risk among pregnant women, based on solely self-reported sexual behaviors [49,50]. Low perceived HIV risk is a common reason for declining PrEP among pregnant women, even when male partner HIV status is unknown [51].…”
Section: Discussionmentioning
confidence: 99%